The Influence of Halal Certification and BPOM Distribution Permit on Purchase Intention of Snack Food Products (Pureats Brand Study) - Anisa Susanti; Nurliya Apriyana (LP2M IAIN Palopo, 2026)
Indonesian consumers' awareness of halal food and food safety is increasing, especially among young parents who choose children's snacks, driven by the USD 184 billion halal market (2021-2022). This study aims to analyze the influence of halal certification and BPOM distribution permit on purchase intention of Pureats products in Greater Jakarta. Using a quantitative explanatory approach with purposive sampling of 100 parents aged 25-40 years with children aged 1-5 years, primary data from Likert scale questionnaires were analyzed using multiple linear regression via SPSS, including validity, reliability, normality, t, F, and R² tests. The results showed that halal certification (β = 0.342, p = 0.016) and BPOM permit (β = 0.439, p = 0.000) had a significant positive effect partially and simultaneously (F = 24.418, p = 0.000), with R² = 33.5%. The conclusion states that both factors shape consumer trust, it is recommended to highlight labels on packaging for marketing strategies.